2017
DOI: 10.5935/1415-2762.20170044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Application Program for the Teaching of Vital Signs

Abstract: RESUMOO objetivo deste estudo é descrever a avaliação pelo público-alvo de um aplicativo de celular construído para o ensino dos sinais vitais. Seguiramse metodologicamente os passos propostos por Galvis-Panqueva para o processo de construção e validação de tecnologias. E neste estudo está descrita a etapa de avaliação pelo usuário. Participaram 29 acadêmicos do curso de graduação de enfermagem, que responderam a um instrumento de avaliação do aplicativo quanto às características de estilo, motivação e conteúd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
5
0
5
Order By: Relevance
“…Such technology is considered a tool that supports management, also unfolding in care and care management, focus of nursing. 7,[16][17] A systematic review that evaluated 17 papers on care management information systems showed that only three integrated data to support clinical decisions, which suggests that computerization is still incipient regarding care. It also emphasizes that professionals need to be updated on the subject in order to avoid the use of technologies only for tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such technology is considered a tool that supports management, also unfolding in care and care management, focus of nursing. 7,[16][17] A systematic review that evaluated 17 papers on care management information systems showed that only three integrated data to support clinical decisions, which suggests that computerization is still incipient regarding care. It also emphasizes that professionals need to be updated on the subject in order to avoid the use of technologies only for tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile apps are tools allied to nurses in the care process. 16 The use of nursing apps must respect aspects inherent to information technologies and should be able to assist nurses in the technical performance of the nursing process, 17 promoting quality and safety for the patient and staff. 18 The measure of the quality of one software regarding what it proposes to accomplish needs to be evaluated by pre-established criteria, evidencing its success for clinical usability.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns pesquisadores validam através de seus estudos que os aplicativos de celular facilitam o entendimento do conteúdo pelo usuário e que os mesmos, fazem do usuário o protagonista do processo de ensino-aprendizado do adulto (1,13,15) .…”
Section: Discussionunclassified
“…ICTs have led to changes in traditional teaching models, reducing barriers to differentiated teaching, overcoming time and space, enabling students to take active learning approaches without passive reception of knowledge, and promoting continuous learning and exchange of experiences and information among the learners. [17][18][19][20][21] In the meantime, ICTs have provided innovations in both teaching and learning processes. 3…”
Section: Information and Communication Technology: Innovation In Teacmentioning
confidence: 99%
“…They integrate functionalities and tools that help in the construction of an online interactive teaching-learning process use internet resources for it. [3][4]17 VLE when combined with technological resources, provides a more reflective, problematic, interactive and collaborative learning, which favors decision making within the hospital practice. 22,24 VLEs have some useful attributes.…”
Section: Object and Virtual Learning Environment: Construction Of Newmentioning
confidence: 99%